Systematic determination of the relationship between nanoparticle core diameter and toxicity for a series of structurally analogous gold nanoparticles in zebrafish. Issue 7 (9th August 2019) - Truong, Lisa; Zaikova, Tatiana; Baldock, Brandi L.; Balik-Meisner, Michele; To, Kimberly; Reif, David M.; Kennedy, Zachary C.; Hutchison, James E.; Tanguay, Robert L.
Abstract: Predictive models for the impact of nanomaterials on biological systems remain elusive. Although there is agreement that physicochemical properties (particle diameter, shape, surface chemistry, and core material) influence toxicity, there are limited and often contradictory, data relating structure to toxicity, even for core diameter. Given the importance of size in determining nanoscale properties, we aimed to address this data gap by examining the biological effects of a defined series of gold nanoparticles (AuNPs) on zebrafish embryos. Five AuNPs samples with narrowly spaced core diameters (0.8–5.8 nm) were synthesized and functionalized with positively charged N, N, N -trimethylammonium ethanethiol (TMAT) ligands. We assessed the bioactivity of these NPs in a high-throughput developmental zebrafish assay at eight concentrations (0.5–50 µg/mL) and observed core diameter-dependent bioactivity. The smaller diameter AuNPs were the most toxic when expressing exposures based on an equal mass. However, when expressing exposures based on total surface area, toxicity was independent of the core diameter. When holding the number of nanoparticles per volume constant (at 6.71 × 10 13 /mL) in the exposure medium across AuNPs diameters, only the 5.8 nm AuNPs exhibited toxic effects. Under these exposure conditions, the uptake of AuNPs in zebrafish was only weakly associated with core diameter, suggesting that differential uptake of TMAT-AuNPs was not responsible for toxicity associated with the 5.8 nm core diameter. Our results indicate that larger NPs may be the most toxic on a per particle basis and highlight the importance of using particle number and surface area, in addition to mass, when evaluating the size-dependent bioactivity of NPs.